The role of heparins and nano-heparins as therapeutic tool in breast cancer - Afratis, N. A.; Karamanou, K.; Piperigkou, Z.; Vynios, D. H.; Theocharis, A. D. (Glycoconj J, 2017)
Glycosaminoglycans are integral part of the dynamic extracellular matrix (ECM) network that control crucial biochemical and biomechanical signals required for tissue morphogenesis, differentiation, homeostasis and cancer development. Breast cancer cells communicate with stromal ones to modulate ECM mainly through release of soluble effectors during cancer progression. The intracellular cross-talk between cell surface receptors and estrogen receptors is important for the regulation of breast cancer cell properties and production of ECM molecules. In turn, reorganized ECM-cell surface interface modulates signaling cascades, which regulate almost all aspects of breast cell behavior. Heparan sulfate chains present on cell surface and matrix proteoglycans are involved in regulation of breast cancer functions since they are capable of binding numerous matrix molecules, growth factors and inflammatory mediators thus modulating their signaling. In addition to its anticoagulant activity, there is accumulating evidence highlighting various anticancer activities of heparin and nano-heparin derivatives in numerous types of cancer. Importantly, heparin derivatives significantly reduce breast cancer cell proliferation and metastasis in vitro and in vivo models as well as regulates the expression profile of major ECM macromolecules, providing strong evidence for therapeutic targeting. Nano-formulations of the glycosaminoglycan heparin are possibly novel tools for targeting tumor microenvironment. In this review, the role of heparan sulfate/heparin and its nano-formulations in breast cancer biology are presented and discussed in terms of future pharmacological targeting.
Afratis, Nikos AKaramanou, KonstantinaPiperigkou, ZoiVynios, Demitrios HTheocharis, Achilleas DengReviewResearch Support, Non-U.S. Gov't2016/10/26Glycoconj J. 2017 Jun;34(3):299-307. doi: 10.1007/s10719-016-9742-7. Epub 2016 Oct 24.
Keywords: *breast cancer; *Gene Expression Regulation, Neoplastic; *Heparan sulfate; *Heparin; *Nano heparin; *Pharmacological targeting; Animals; Antineoplastic Agents/chemistry/*therapeutic use; Breast Neoplasms/*drug therapy/genetics/metabolism/pathology; Cell Communication/drug effects; Cell Line, Tumor; Cell Proliferation/drug effects; Cytokines/genetics/metabolism; Extracellular Matrix/chemistry/metabolism; Female; Heparin/*chemistry/therapeutic use; Heparitin Sulfate/chemistry/*therapeutic use; Humans; Intercellular Signaling Peptides and Proteins/genetics/metabolism; Protein Binding/drug effects; signal transduction; Stromal Cells/drug effects/metabolism/pathology